Um ensino de Física diferenciado para o ENEM - PEREIRA, Adalto Ferreira (2020)
This work originated from a question: "what do you think about physics" that highlighted Physics as a discipline little understood by students, all thanks to the different factors of which we can mention the pedagogical common sense. We report here what made the National High School Exam (Enem) such a comprehensive exam, to the point of being considered one of the largest entrance exams in the world, and what the Anísio Teixeira Institute (INEP), through the Reference Matrix (MR) do Enem expects about teaching in Brazil. Aims to show a way of teaching with the use of educational software Phet and ALGODOO and visitation to the Physics laboratory of the Federal University of Pará (UFPA), as teaching assistants in the classroom, proposal is applied in 2019 in the Pre-Enem project from the Ananindeua / UFPA campus that aims at Enem.